Overview of Governance for Resilience (G4R) - Amarnath, Giriraj (CGIAR System Organization, 2022)
This technical brief explains the concept behind ClimBeR’s Governance 4 Resilience (G4R) research, which aims to develop governance systems that promote cross-societal resilience to climate change.